Britain’s foreign policy towards European countries From the Spanish War of Succession to the end of the Seven Years’ War (1701-1763) - AL-Zuhair, Rana Abdul Jabar H. (Al-Adab Journal, 2022)
This research Paper discusses the Britain’s foreign policy towards the European countries during the period between 1701-1763, that is, from the War of the Spanish Succession until the end of the Seven Years’ War. It was divided into three chapters: Chapter one showed the British policy towards European countries during the period between (1701-1721), while the second topic dealt with the nature of the foreign policy adopted by the British government during the period (1721 - 1748), indicating the active role exercised by Prime Minister Sir Robert Walpole in that policy, the third section of the research has been allocated To study British foreign policy towards the most important Happenings in Europe during the period (1748-1763). The conclusion of the study was the most important of the results.